IMPLEMENTASI MODEL PEMBELAJARAN LEARNING CYCLE 5E UNTUK MENINGKATKAN HASIL BELAJAR KOGNITIF IPAS MATERI MENGUBAH BENTUK ENERGI PADA PESERTA DIDIK KELAS IV A DI SDN SRONDOL KULON 02 SEMARANG - Nur Yuliyanty; Nursiwi Nugraheni; Teguh Budi Prakoso (STKIP Subang, 2024)
The problem in this research is the low learning outcomes of students in class IVA at SDN Srondol Kulon 02. After conducting classroom observations, the cause of the low learning outcomes is that teachers only tend to use the lecture learning method with the only learning source being textbooks. This encourages researchers to apply the 5E learning cycle learning model with various learning methods so that it is expected to be more effective than lectures. The aim of this research is to determine the implementation of the 5E learning cycle learning model effectively to improve cognitive learning outcomes in science and technology, material changing the form of energy for class IV A students at SDN Srondol Kulon 02 Semarang. This type of research is classroom action research. The data source used is quantitative data in the form of test data on students' cognitive learning outcomes which are analyzed using descriptive analysis techniques by determining the average. Based on the research results, it was found that the average grade for class I in cycle I was 67, rising to 74 in cycle II, and rising to 81 in cycle III. The level of classical completion also increased, namely in cycle I it got 32.1%, then cycle II got 60.7% and cycle III got 92.9%. The results of this research can prove that the 5E learning cycle learning model is effective in improving the cognitive learning outcomes of class IV A Srondol Kulon 02 Semarang students.